2019
DOI: 10.1002/cssc.201902071
|View full text |Cite
|
Sign up to set email alerts
|

Review on Recent Progress in the Development of Tungsten Oxide Based Electrodes for Electrochemical Energy Storage

Abstract: Current progress in the advancement of energy‐storage devices is the most important factor that will allow the scientific community to develop resources to meet the global energy demands of the 21st century. Nanostructured materials can be used as effective electrodes for energy‐storage devices because they offer various promising features, including high surface‐to‐volume ratios, exceptional charge‐transport features, and good physicochemical properties. Until now, the successful research frontrunners have fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(85 citation statements)
references
References 178 publications
(306 reference statements)
2
83
0
Order By: Relevance
“…47 Shinde et al, in 2020, explained the pH-and potential-dependent behavior of tungsten in an aqueous medium, as well as the tungsten oxide crystal structures. 48 Various tungstate trioxide-based materials have been synthesized and tested extensively. However, tungstate trioxide has a low energy density and surface area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Shinde et al, in 2020, explained the pH-and potential-dependent behavior of tungsten in an aqueous medium, as well as the tungsten oxide crystal structures. 48 Various tungstate trioxide-based materials have been synthesized and tested extensively. However, tungstate trioxide has a low energy density and surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more research is required to enhance their performance as active electrode materials. 48 Wet chemical synthesis is one of the widely used techniques for the synthesis of NPs, which commonly deals with the chemical reaction occurring in its solution phase. Of the many methods available for the synthesis of NPs such as solvothermal and template synthesis, oriented attachment, self-assembly, etc., the wet chemical synthesis method offers a high degree of material reproducibility and controllability.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst reportedly performed better than pure Ni/NiO in terms of its Tafel slope, as the former reached 152 mV/dec, whereas for the latter the Tafel slope was reported to be 244 mV/dec elsewhere [101]. Tungsten dioxide (WO2) or trioxide (WO3) or suboxides (WO3-x) are known to have high metallic conductivity, and these are among the lucrative options in transition metal oxide groups [102]. However, they are prone to transform into tungsten carbide in high carbon concentration, and hence it is very difficult to synthesize them with CNFs, while carbonizing and yet retaining the suboxide structure [103].…”
Section: Cnf Supported Metal Oxidesmentioning
confidence: 99%
“…Chen et al, (2016) [104] had demonstrated a novel technique to incorporate WO3-x in a controlled manner on the electrospun CNFs, where with the increment of tungsten precursor, the suboxide tended to increase, reducing the carbide formation. The study suggested that as the percent of precursor increased in the electrospinning solution, the HER activity increased in 0.5 M H2SO4 solutions, and with 30% of metal precursor the Tafel slope, this was found to be 89 Tungsten dioxide (WO 2 ) or trioxide (WO 3 ) or suboxides (WO 3-x ) are known to have high metallic conductivity, and these are among the lucrative options in transition metal oxide groups [102]. However, they are prone to transform into tungsten carbide in high carbon concentration, and hence it is very difficult to synthesize them with CNFs, while carbonizing and yet retaining the suboxide structure [103].…”
Section: Cnf Supported Metal Oxidesmentioning
confidence: 99%
“…23,24 It is cost-effective and has excellent physical and chemical properties such as an n-type wide band gap, high density (7.13 g cm À3 ), various oxidation states (W 2+ -W 6+ ), and variable electrical conductivity (10-10 À6 S cm À1 ). 25,26 Also, WO 3 exists in various crystalline phases which makes WO 3 an extraordinary material amongst other TMOs for electrochromic, photocatalytic, gas sensing and electrochemical energy storage application. [27][28][29][30][31] Moreover, the various crystal phases including trigonal tunnels and cavities are highly favorable for tuning its physical properties and electrochemical ion intercalation.…”
Section: Introductionmentioning
confidence: 99%